Do Entrepreneurial Orientation, Product Quality, and Marketing Strategy Influence the Business Performance of Mega Furniture Store Bireuen - Aceh? - Azmi Azmi; Zainuddin Iba; Irne Aryanie (Singkite Journal, 2026)
In the study of entrepreneurial performance, particularly in the furniture sales business, creative innovation is required in business orientation, product selection, and marketing systems. This ensures sustainability in entrepreneurship. An associative survey research was implemented with a quantitative approach. The problem analysis used a statistical tool, namely the path analysis model. The research sample was taken using non-probability sampling with a purposive sampling method, totaling 100 customers. The research results revealed: (1) Business performance is influenced by the causality of three factors: entrepreneurial orientation, product quality, and marketing strategy, both directly and indirectly. (2) The contribution of each aspect of entrepreneurial orientation is 22.43%, product quality 35.15%, and marketing strategy 35.15%. 2) There are direct and indirect influences, so the effect can be calculated at 20.75%. (3) The simultaneous contribution of these three factors to business performance at the Mega Furniture Store in Bireuen Regency is 36.4%.